The effect of facial hair whorl position and raising environment on the temperament of the Chinese Yellow cattle in Shinjang Uyghur Aptonom Rayoni, China (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study is to determine whether there is a relationship between hair whorl position and temperament in Chinese Yellow cattle using a questionnaire. Also, the effect of the raising environment is investigated.  Materials and methods: A total of 122 Chinese Yellow cattle were surveyed in 3 village areas and four grassland areas in the northern area of China. For each cattle, an investigator asked the care-person about each item of a temperament questionnaire and determined the facial hair whorl position of each cattle. The location of hair whorl was categorized as low, middle, or high in relation to the eyes.  Results: The overall distribution was 20.5% high, 58.2% middle, 13.1% low, 6.6% double, and 1.6% no hair whorl. There was no significant difference between the grassland and village area cattle in the distribution of whorl position. The scores of grassland areas were significantly higher than those of village areas in terms of “Retentive memory”, “Sensitivity,” and “Timidity” and lower in “Docility” and “Fortitude.” The scores for the high position tended to be higher than those for the middle plus low positions in terms of “Adaptability” and “Obedience.” On the other hand, there was a tendency for a score for the high position to be lower than the other positions in “Excitability.” A significant interaction between area and whorl position was observed in “Friendliness to cattle.”  Conclusion: These findings suggest that hair whorl location may be useful in predicting the temperament in cattle, but temperament can be influenced by environment and/or handlings.J. Adv. Vet. Anim. Res., 7(3): 477-481, Sep 2020http://doi.org/10.5455/javar.2020.g444